Generalized Differentiable E-Invex Functions and Their Applications in Optimization. (2nd October 2012) - Jaiswal, S.; Panda, G.
Abstract : The concept of E -convex function and its generalizations is studied with differentiability assumption. Generalized differentiable E -convexity and generalized differentiable E -invexity are used to derive the existence of optimal solution of a general optimization problem.